Histoire des techniques en canoë-kayak freestyle - Terret, C.; Robène, L.; Grosjean, B. (Movement & Sport Sciences - Science & Motricité, 2017)
The aim of freestyle canoeing is the realization of moves in rivers' waves. When we compare techniques used in 1991, during the first World's championships, with those performed today, we can note a difference. The purpose of this study is to determine, from the cultural technology viewpoint, the mechanisms which have led to a fast evolution of the moves. Our methodology is based on the analysis of "Canoë Kayak Magazine", videotapes, and on an interview. Our results show that the concept of motor logics, stated by Vigarello (1988), perfectly applies to freestyle moves. The moves performed by the paddlers are increasingly aerial, quick, fluid and connected. This transformation is due to various phenomena in interrelationships. A material better fitted to the practice, and particularly shorter boats whose shape has evolved, made possible the fact to ease the execution of the moves. The fun aspect, but also the implication of brands on this growth market, promoted the paddlers' spirit of creation as well technically as materially. Finally, the rulebook, after having followed the technical changes, radically changed to allow to the candidates to diversify their techniques. However, this expansion was partly slowed down by the practise of traditional disciplines.